The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.2307/1552131
|View full text |Cite
|
Sign up to set email alerts
|

Soils and Cryoturbation in Moist Nonacidic and Acidic Tundra in the Kuparuk River Basin, Arctic Alaska, U.S.A.

Abstract: Douglas and Tedrow (1960) were the first to report calcareous tundra soils in northern Alaska. Soils adjacent to the Sagavanirktok River were consistently alkaline. Calcareous soils derived from loess and lacustrine materials occur throughout the Prudhoe Bay region (Everett, 1975; Everett and Parkinson, 1977; Parkinson, 1978). Walker and Everett (1991) collected soil samples along a 20-km loess gradient downwind of the Sagavanirktok River, showing the effects of loess deposition on particlesize distribution, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 21 publications
3
65
2
Order By: Relevance
“…This area has a mean July temperature of 11°C, a mean January temperature of -22°C, and 325 mm mean annual precipitation (Zhang et al, 1996). The Upper Capsule watershed is currently dominated by moist dwarf-shrub tussock-graminoid tundra (Walker et al, 1994;Muller et al, 1999), with moist, acidic, organic soils (Bockheim et al, 1998). The site is underlain by continuous permafrost, with a shallow thaw layer (e.g., Walker et al, 2001).…”
Section: Study Sitesmentioning
confidence: 99%
“…This area has a mean July temperature of 11°C, a mean January temperature of -22°C, and 325 mm mean annual precipitation (Zhang et al, 1996). The Upper Capsule watershed is currently dominated by moist dwarf-shrub tussock-graminoid tundra (Walker et al, 1994;Muller et al, 1999), with moist, acidic, organic soils (Bockheim et al, 1998). The site is underlain by continuous permafrost, with a shallow thaw layer (e.g., Walker et al, 2001).…”
Section: Study Sitesmentioning
confidence: 99%
“…There are no obvious patterned ground features at either site. Although separated by only 4 kilometers, they are dissimilar with respect to plant diversity, soil pH, mean thaw depth, and near-surface soil moisture content (Bockheim et al 1997(Bockheim et al , 1998Hinkel et al 2000;Walker, Walker, and Auerbach 1994;Walker, Auerbach, and Shippert 1995;). Site FSP 95-4 is in moist acidic tundra characterized by grassy tussocks spaced less than 1 meter apart.…”
Section: Description Of Sitesmentioning
confidence: 99%
“…Moist non-acidic tundra is present not only on recently deglaciated landscapes, but also on landscapes with high inputs of loess or lacustrine materials and a high degree of cryoturbation (Walker and Everett 1991;Bockheim et al 1998;Walker et al 1998). Previous research comparing plant biomass and soil nutrients on loess-dominated acidic and non-acidic tundra showed that aboveground biomass of Carex bigelowii, Hylocomium splendens, and Cassiope tetragona from nonacidic sites had higher concentrations of calcium (Ca) than biomass of those species from acidic sites, reflecting soils with high amounts of extractable Ca and high base saturation .…”
Section: Introductionmentioning
confidence: 99%